2015
DOI: 10.1038/srep15570
|View full text |Cite
|
Sign up to set email alerts
|

Environmental neurotoxin interaction with proteins: Dose-dependent increase of free and protein-associated BMAA (β-N-methylamino-L-alanine) in neonatal rat brain

Abstract: β-Methylamino-L-alanine (BMAA) is implicated in the aetiology of neurodegenerative disorders. Neonatal exposure to BMAA induces cognitive impairments and progressive neurodegenerative changes including intracellular fibril formation in the hippocampus of adult rats. It is unclear why the neonatal hippocampus is especially vulnerable and the critical cellular perturbations preceding BMAA-induced toxicity remains to be elucidated. The aim of this study was to compare the level of free and protein-associated BMAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Previous studies in rodents revealed that BMAA is taken up in tissues characterized by a high protein synthesis, i.e. in intestinal epithelium, bone marrow, lymphatic tissues such as thymus and spleen, and liver (Karlsson et al, 2009a, Andersson et al, 2013, Karlsson et al, 2014, Karlsson et al, 2015b. In accordance with these data, about 1 and 6 % of the BMAA recovered from adult rat liver and brain were released following protein hydrolysis.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies in rodents revealed that BMAA is taken up in tissues characterized by a high protein synthesis, i.e. in intestinal epithelium, bone marrow, lymphatic tissues such as thymus and spleen, and liver (Karlsson et al, 2009a, Andersson et al, 2013, Karlsson et al, 2014, Karlsson et al, 2015b. In accordance with these data, about 1 and 6 % of the BMAA recovered from adult rat liver and brain were released following protein hydrolysis.…”
Section: Discussionsupporting
confidence: 84%
“…Amongst the more reently discussed copounds with a potential to cause DNT is paracetamol (Brandlistuen et al, 2013; Liew et al, 2014; Viberg et al, 2014), but it is not clear yet whether this effect is direct or whether it requires metabolic activation. There are also indictions that the food-borne non-proteinogenic amino acid BMAA affects neurodevelopment (Karlsson et al, 2015). The same is true for acrylamide, a chemical generated from amino acid precursors during food processing (Duarte-Salles et al, 2013; Pedersen et al, 2012).…”
Section: Challenges Encountered During the Search For Reference Commentioning
confidence: 99%
“…Amongst the more recently discussed compounds with a potential to cause DNT is paracetamol (Brandlistuen et al, 2013;Liew et al, 2014;Viberg et al, 2014), but it is not clear yet whether this effect is direct or whether it requires metabolic activation. There are also indications that the food-borne non-proteinogenic amino acid BMAA affects neurodevelopment (Karlsson et al, 2015). The same is true for acrylamide, a chemical generated from amino acid precursors during food processing (Duarte-Salles et al, 2013;Pedersen et al, 2012).…”
Section: Examples Of Other Compounds Not Considered Herementioning
confidence: 93%